The Effect of Statins on Clinical Outcome Among Hospitalized Patients With COVID-19: A Multi-Centric Cohort Study - Umakanthan, Srikanth; Senthil, Sanjum; John, Stanley; Madhavan, Mahesh K.; Das, Jessica; Patil, Sonal; Rameshwaram, Raghunath; Cintham, Ananya; Subramaniam, Venkatesh; Yogi, Madhusudan; Bansal, Abhishek; Achutham, Sumesh; et al. (Frontiers in Pharmacology, 2022)
Purpose: The association of COVID-19 infection in a high proportion of patients suffering from co-morbidities (hypertension, diabetes mellitus, and coronary artery disease) is well documented in the literature. These patients are usually on statin therapy to avoid progression into a life- threatening complications. We evaluated the effects of statins on COVID-19 hospitalized patients using a retrospective matched cohort to reduce the effects of confounding factors on the population. Study design: This is a multi-centric retrospective cohort study. This study was conducted across three multispecialty hospitals in South India. We included 1626 patients diagnosed with COVID-19 and hospitalized from June 1st, 2020 to April 30th, 2021. The inclusion criteria for the study population were COVID-19 patients hospitalized, discharged, or died during the above-mentioned period. Patients below the age of 18 and above 80 years, those without proper documentation of medical records, patients admitted for only one day, and those suffering from tuberculosis, hepatitis B, HIV, and carcinomas requiring immunomodulatory therapies were excluded. Results: This study comprised 1626 COVID-19 patients, of whom 524 (32.2%) were on statins with 52.4% being males. The comorbidity prevalence of hypertension was 75%, followed by diabetes 62.51% and coronary artery disease being 47.5%. At the time of hospitalization, statin users had a higher incidence of dyspnea, cough, and fatigue (95.8%, 93.3%, and 92.7%). The laboratory results revealed a lower mean of WBC count (7.6x103/µL), D-dimer (2.1µg/ML), and C-reactive protein (100 mg/L) among statin users. They also had lower mortality rates (17.1%), a lesser requirement for mechanical ventilation (20%), and hemodialysis (5.4%). Conclusion: This observation study elaborates the beneficial effects of statins in COVID-19 patients. The main effect of bias in cohort studies was eliminated by using propensity match scores so as to provide efficient results.